Can Preoperative Imaging Predict Tumor Involvement of the Anterior Clinoid in Clinoid Region Meningiomas?. Issue 4 (26th June 2015) - Copeland, William R.; Van Gompel, Jamie J.; Giannini, Caterina; Eckel, Laurence J.; Koeller, Kelly K.; Link, Michael J.
Abstract : BACKGROUND: Anterior clinoid region meningiomas may infiltrate the bone over which they arise, therefore requiring an anterior clinoidectomy to achieve a Simpson grade 1 resection. A clinoidectomy, however, is not without risks. OBJECTIVE: We performed a study of diagnostic accuracy investigating whether preoperative imaging could predict tumor involvement of the clinoid, and thereby tailor the degree of bony removal. METHODS: Patients having undergone resection of a clinoid region meningioma between 2001 and 2011 were identified. Included in further analysis were those patients in whom a clinoidectomy was performed with subsequent pathologically confirmed presence or absence of tumor in the clinoid process on decalcified specimens. Two neuroradiologists, blinded to pathology results, independently reviewed available preoperative imaging and stated whether or not they anticipated the clinoid to be involved by tumor. Interobserver agreement and the ability to accurately predict tumor involvement of the clinoid were then analyzed. RESULTS: Sixty-two patients were included in the final analysis. Interobserver agreement was 100%. Sensitivity and specificity of preoperative imaging to predict tumor involvement was 89% and 52%, respectively, with positive and negative likelihood ratios of 1.85 and 0.20. Positive and negative predictive values were 73% and 76%, respectively. CONCLUSION: Preoperative imaging of clinoid region meningiomas can accurately predict the presence or absence of tumor involvement of the clinoid in only approximately 75% of cases. In light of the fact that a quarter of patients with radiographically negative clinoids will have tumor present on pathological analysis, we recommend a clinoidectomy for all clinoid region meningiomas.